Interprofessional Practice: Beyond Competence - Flood, B; Smythe, E; Hocking, C; Jones, M (Springer Verlag, 2019)
Interprofessional practice is commonly discussed in the literature in terms of competencies. In this study we move away from the theoretical notions of criteria, concepts and guidelines to adopt an ontological approach which seeks to stay as close to the lived experience as possible. Our research asked 12 participants from a variety of health disciplines to tell their stories of working interprofessionally. We sought to glean meaning from the lived experience. Our phenomenological hermeneutic approach and interpretation were informed by Heidegger and Gadamer. Rather than offering a thematic overview, in this article we share three stories from the research that were congruent with other stories. The first, told by a doctor, is of a resuscitation in an emergency department. It shows how the effective working together of the interprofessional team was more than each member following a resuscitation protocol. There was ‘something’ about how they worked together that made this story stand out, even though the patient died. The second story showcases how ‘who’ the person is makes a difference. This nurse makes an effort to get to know other staff as people, to find common interests. In such a way interprofessional practice comes to flourish. The third story shows how a physiotherapist and a psychologist joined in conversation to seek innovative possibilities for a challenging situation. In such a way each built on the others expertise and were excited at the success they achieved for the patient. From these ontological accounts we have come to see that interprofessional practice flourishes when practitioners are their authentic, caring selves. Who the person is matters.
Keywords: Competency; Interprofessional practice; Phenomenology; Health professional education